Lead-free perovskite Cs2NaHoBr6 and fractal structure, preparation method and application thereof

By using water as a solvent and evaporation treatment to form a fractal structure in the preparation of lead-free perovskite Cs2NaHoBr6, the problem of using toxic bromic acid solvent and high temperature and high pressure in traditional methods is solved, and the green preparation of the material and efficient thermal retardation is achieved. Destroy and temperature sensing properties.

CN119461460APending Publication Date: 2025-02-18SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411610870.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing preparation methods for lead-free perovskite materials often use toxic bromic acid solvents, which lead to threats to the environment and human health. At the same time, traditional materials are prone to fluorescence heat quenching at high temperatures, affecting the accuracy of temperature measurement.

Method used

Using water as a solvent, lead-free perovskite Cs2NaHoBr6 is prepared by heating the solution of sodium bromide, cesium bromide and holmium bromide, and crystals with fractal structure are formed by evaporation, avoiding the use of toxic bromic acid solvents and high temperatures. High pressure conditions.

Benefits of technology

The green preparation of lead-free perovskite Cs2NaHoBr6 was achieved, which overcomes the environmental and health hazards in traditional methods, and significantly improves the anti-thermal quenching and temperature sensing performance of the material, and has the ability to convert up and down conversion luminescence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461460A_ABST
    Figure CN119461460A_ABST
Patent Text Reader

Abstract

The invention discloses lead-free perovskite Cs2NaHoBr6 as well as a fractal structure, a preparation method and application thereof, and belongs to the technical field of photoluminescence and fractal crystal growth. The lead-free perovskite Cs2NaHoBr6 is successfully synthesized through a novel solvent boiling method, and compared with a traditional fluorescence thermal quenching perovskite material, the lead-free perovskite shows thermally enhanced red light and near infrared light emission under excitation of ultraviolet light, blue light and near infrared light, has up-conversion and down-conversion luminescence capabilities, and can be used for preparing a luminescent material. The emission peak intensity is in positive correlation in the range of 293-593 K, and an abnormal heat quenching resistance behavior is shown. Cs2NaHoBr6 powder is dissolved in an anti-solvent, and a fractal structure pattern with preferred orientation and self-similarity characteristics is prepared by using an in-situ solution crystallization method, so that the temperature sensing performance of the compound is remarkably improved, the relative sensitivity of the compound is enhanced from 1.14% K <-1 > to 2.60% K <-1 >, and the compound shows a good application prospect in the aspect of non-contact optical temperature measurement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoluminescence and fractal crystal growth, and specifically relates to a lead-free perovskite Cs2NaHoBr6 and its fractal structure, preparation method and application. Background Art

[0002] In the field of luminescent materials, halogen perovskite structures have attracted much attention due to their unique optoelectronic properties. However, the toxicity and environmental issues of traditional lead-based halogen perovskite materials limit their widespread use in biomedical and environmentally friendly applications. In addition, traditional halogen perovskite preparation methods often involve the use of toxic hydrogen bromide solvents, which not only pose a threat to the environment but also pose a potential risk to the health of operators. Fractals are a class of structures with preferential orientation and self-similarity, which are widely present in all things in nature, such as mountains, coasts, snowflakes, and human neural networks. The self-similarity of fractal structures can increase the surface area of ​​materials, optimize heat distribution, and improve the scattering and reflection of light, making the material respond to temperature changes faster, thereby improving the sensitivity and accuracy of optical temperature sensors, achieving higher sensing performance, and providing new ideas for the design of high-performance optical temperature sensors.

[0003] So far, there are patents related to Cs2NaHoCl6 compounds in halogen perovskite materials under application, mainly including Chinese patent applications CN202410085804.X, CN202311000904.X, CN202410753947.3, CN202310937826.X, etc., but there are no reports on the synthesis process of Cs2NaHoBr6 compounds and patents related to their unique properties. Especially from the perspective of crystal growth, there is still a blank in the world's reports on the growth of fractal structures of halogen perovskites. In particular, there are no published papers or patents on the growth of fractal structures of lead-free perovskite Cs2NaHoBr6. The introduction of fractal structure not only improves the optical properties of the material, but also enhances the stability and durability of the material. Its unique up- and down-conversion luminescence characteristics make the material have broad application prospects in the field of photoelectric conversion. In addition, the preparation method of the fractal structure is simple and low-cost, which is conducive to promoting the commercialization process of the material. From the application perspective, non-contact fluorescence temperature sensing is widely used for temperature measurement due to its advantages such as high sensitivity, fast response time and avoidance of direct contact. Nevertheless, traditional fluorescence temperature sensing materials will exhibit fluorescence thermal quenching at high temperatures, which seriously affects the accuracy of optical temperature measurement. Therefore, it is increasingly urgent to enhance the anti-thermal quenching and temperature sensing performance of perovskite luminescent materials under high temperature conditions. At present, it is still a common method to adjust the optical properties of materials by incorporating lanthanide elements as activators. However, since the ionic radius of lanthanide elements is usually significantly different from that of the main elements and the doping amount is often very limited, it may lead to lattice mismatch, low energy transfer efficiency and fluorescence quenching due to excessive doping concentration.

[0004] The development of a perovskite luminescent material that does not require doping and has anti-thermal quenching properties has become the key to achieving non-contact temperature measurement under high temperature conditions. In addition, the various methods for preparing lead-free perovskites that have been reported mainly focus on solvothermal method, hot injection method, ligand-assisted reprecipitation method, etc., and there are certain limitations in the synthesis process, which restricts its large-scale synthesis in industry, such as: the use of highly environmentally hazardous and biologically toxic reagents, the need for high pressure conditions, complex preparation process, and long preparation time. Therefore, finding a preparation process without high pressure, fast synthesis, and non-toxicity is the key to achieving large-scale production of lead-free perovskite materials. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a lead-free perovskite Cs2NaHoBr6 and its fractal structure, preparation method and application, so as to solve the technical problem that bromic acid needs to be added during the synthesis process of the existing preparation method, which brings harm to the environment and human body.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a preparation method of lead-free perovskite Cs2NaHoBr6, comprising: firstly completely dissolving a sodium-containing compound, a cesium-containing compound and a holmium-containing compound in water, then heating until the solvent is evaporated, and cooling to room temperature to obtain the lead-free perovskite Cs2NaHoBr6.

[0007] Preferably, the molar ratio of the sodium-containing compound, the cesium-containing compound and the holmium-containing compound is 1:2:1; the sodium-containing compound is sodium bromide; the cesium-containing compound is cesium bromide; and the holmium-containing compound is holmium bromide.

[0008] Preferably, the heating temperature is 373-593 K.

[0009] The invention also discloses a lead-free perovskite Cs2NaHoBr6, which is prepared by the above preparation method.

[0010] Preferably, the lead-free perovskite Cs2NaHoBr6 emits red light of 620-680 nm and near-infrared light of 950-1020 nm under short-wave ultraviolet light or blue light excitation; emits red light of 620-680 nm and near-infrared light of 760-820 nm when excited by near-infrared light; the emission peak intensity of the lead-free perovskite Cs2NaHoBr6 shows a positive correlation in the range of 293-593 K.

[0011] Preferably, the method comprises: completely dissolving the lead-free perovskite Cs2NaHoBr6 in water to obtain a transparent solution, adding an anti-solvent to disperse the solution evenly, placing the solution on a substrate material, and obtaining an ordered fractal structure after crystallization.

[0012] The invention also discloses a method for preparing a fractal structure of a lead-free perovskite Cs2NaHoBr6. The solubility of the transparent solution is 50-100 mg / mL. The dosage ratio of the lead-free perovskite Cs2NaHoBr6 to the anti-solvent is (100-300) mg: (1-2) mL.

[0013] Preferably, the anti-solvent is anhydrous ethanol, isopropanol, n-propanol, acetone or tetrahydrofuran; the substrate material is ordinary glass, ITO glass, FTO glass, silicon wafer or silicon wafer containing an oxide layer; and the crystallization temperature is 293-373 K.

[0014] The present invention also discloses a fractal structure of lead-free perovskite Cs2NaHoBr6, which is prepared by the above preparation method. Compared with the lead-free perovskite Cs2NaHoBr6, the relative sensitivity is increased from 1.14% K -1 Enhanced to 2.60% K -1 .

[0015] The present invention also discloses the application of the fractal structure of the lead-free perovskite Cs2NaHoBr6 prepared by the preparation method in the preparation of up-conversion luminescent materials, down-conversion luminescent materials and temperature sensing materials.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of lead-free perovskite Cs2NaHoBr6. The following is the chemical equation of the reaction: 2CsBr+NaBr+HoBr3→Cs2NaHoBr6. The method uses sodium bromide, cesium bromide and holmium bromide as raw materials and water as solvent, avoiding the use of hydrobromic acid with high volatility and toxicity as solvent. Lead-free perovskite Cs2NaHoBr6 with regular block morphology under microscopic morphology is precipitated by heating and evaporation. From the reaction principle, it can be seen that the green method provided by the invention has multiple beneficial effects, which are discussed as follows: ① Mild reaction conditions: Since the method does not require high temperature and high pressure conditions, damage to raw materials and equipment caused by high temperature and high pressure can be avoided, and energy consumption in the reaction process is also reduced. ② Stability of raw materials: Reaction at a lower temperature can reduce the decomposition of raw materials and the occurrence of side reactions, thereby improving the utilization rate of raw materials and the purity of products. ③ Easy to control reaction temperature: Through precise temperature control, the crystal growth process can be optimized to obtain high-quality Cs2NaHoBr6 crystals. ④ Low equipment requirements: Compared with the high-temperature synthesis method that requires special high-pressure equipment, this synthesis method has lower equipment requirements, which reduces production costs and makes large-scale production more economical and feasible. ⑤ Environmentally friendly: Water as a solvent is an environmentally friendly choice because it is non-toxic, readily available and easy to handle. ⑥ Controllability of crystal growth: This synthesis method can very conveniently control the growth of crystals, thereby obtaining Cs2NaHoBr6 crystals with specific morphologies (such as regular fractal structure morphology). ⑦ Scalability of the synthesis process: This synthesis method is simple to operate, easy to scale up, and suitable for industrial production. ⑧ Reduced safety risks: Compared with the high-temperature synthesis method, this synthesis method is carried out at a lower temperature, reducing safety risks during operation. ⑨ Cost-effectiveness: Due to the simple operation, low equipment requirements and high raw material utilization rate of this synthesis method, the overall production cost is low and has better cost-effectiveness. Compared with the high-temperature synthesis method, the reaction conditions of this method are milder, and the reaction temperature is easy to control, which avoids the damage and decomposition of chemical substances caused by high temperature and high pressure, ensures the stability of reactants during the preparation process, and has low equipment requirements. Different from the traditional lead-free perovskite preparation method with the addition of bromic acid, the present invention does not add environmentally harmful and biologically toxic reagents, is safe and green, and is suitable for large-scale industrial synthesis. The harm caused by the synthesis process to the environment and human body is reduced. The lead-free perovskite Cs2NaHoBr6 prepared by the present invention overcomes the fluorescence thermal quenching effect of traditional perovskite materials, exhibits the characteristic that the fluorescence intensity increases with the increase of temperature, has excellent anti-thermal quenching, and realizes double conversion luminescence under undoped conditions.

[0017] The present invention also discloses a lead-free perovskite Cs2NaHoBr6 prepared by the above-mentioned preparation method. The lead-free perovskite Cs2NaHoBr6 prepared by the present invention can realize up-conversion and down-conversion luminescence without doping. Under the excitation of short-wave ultraviolet light or blue light, it emits red light with a wavelength range of 620-680 nm and near-infrared light with a wavelength range of 950-1020 nm; under the excitation of near-infrared light, it emits red light with a wavelength range of 620-680 nm and near-infrared light with a wavelength range of 760-820 nm.

[0018] The present invention proposes for the first time a method for preparing a fractal structure of a lead-free perovskite Cs2NaHoBr6. The method enriches the solute concentration in the droplet by evaporation treatment. Due to the factors of temperature gradient and uneven concentration distribution, the crystal grows in a certain direction, forming a self-similar fractal structure with a preferred orientation. This unique structure can increase the surface area of ​​the material, optimize heat distribution, and improve the scattering and reflection of light, so that the material responds to temperature changes faster, thereby improving the sensitivity and accuracy of the optical temperature sensor and achieving higher sensing performance. This method not only avoids the use of toxic lead elements, but also innovatively avoids the use of toxic hydrogen bromide solvents. By adopting an environmentally friendly synthesis strategy, the Cs2NaHoBr6 fractal structure prepared by this method exhibits excellent down-conversion luminescence characteristics, providing a new choice for the application of luminescent materials. It provides new ideas and methods for the research and application of lead-free perovskite materials, and its fractal structure can further enhance the temperature sensitivity of lead-free perovskites. This lead-free and non-toxic preparation method not only reduces the risks to the environment and health, but also broadens the application prospects of perovskite materials in the fields of safety and environmental protection, and has important scientific significance and market potential.

[0019] The present invention also discloses a fractal structure of a lead-free perovskite Cs2NaHoBr6 prepared by the above preparation method. By growing the lead-free perovskite Cs2NaHoBr6 with an ordered fractal structure, the relative temperature sensitivity of the perovskite is increased from 1.14% K to 0.14% K of the previous disordered powder. -1 Increased to 2.60% K -1 The present invention provides a new idea for anti-thermal quenching materials and improving optical temperature sensing performance, and has high research and application value.

[0020] The present invention also discloses the application of a fractal structure of a lead-free perovskite Cs2NaHoBr6 prepared by the above-mentioned preparation method in the preparation of up-conversion luminescent materials, down-conversion luminescent materials and temperature sensing materials. It can convert low-energy near-infrared light into high-energy red light and near-infrared light of another band. This up-conversion process is not only efficient, but also avoids the common lead pollution problem in traditional up-conversion materials, so that the material has a significant improvement in safety and environmental protection. Under the excitation of short-wave ultraviolet light or blue light, red light and near-infrared light can be emitted, realizing down-conversion luminescence in a wide spectral range. This down-conversion characteristic is of great significance for improving the luminous efficiency and color saturation of LEDs. Compared with traditional down-conversion luminescent materials, the present invention avoids the use of toxic lead elements and hydrogen bromide solvents, making the material more environmentally friendly and safe during preparation and use, which conforms to the concept of modern green chemistry. By growing an ordered fractal structure of lead-free perovskite Cs2NaHoBr6, the temperature sensitivity of the material is significantly improved, so that it has great application potential in the field of optical temperature sensing. It overcomes the fluorescence thermal quenching effect of traditional perovskite materials and shows that the fluorescence intensity increases with the increase of temperature. This anti-thermal quenching property makes the application of the material more stable and reliable in high temperature environments, and broadens the scope of use of temperature sensing materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the XRD pattern of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 1; Figure 2 is the photoluminescence spectrum of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 2 under ultraviolet light and blue light excitation; Figure 3 is the photoluminescence spectrum of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 2 under near-infrared excitation; Figure 4 This is the up-conversion temperature-variable spectrum of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 3 under the excitation of a 980 nm light source; Figure 5 This is the down-conversion temperature-variable spectrum of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 3 under the excitation of a 460 nm light source; Figure 6 is a scanning electron microscope photograph of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 4; Figure 7 is a scanning electron microscope photograph of the fractal structure of the lead-free perovskite Cs2NaHoBr6 obtained in Example 4; Figure 8This is the down-conversion temperature-variable spectrum of the fractal structure of the lead-free perovskite Cs2NaHoBr6 obtained in Example 4 under the excitation of a 460 nm light source; Fig. 9 This is a relative sensitivity comparison diagram of the fractal structure of the lead-free perovskite Cs2NaHoBr6 and the disordered powder obtained in Example 5. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0024] The present invention is further described in detail below in conjunction with the accompanying drawings: The present invention provides a method for preparing lead-free perovskite Cs2NaHoBr6, comprising the following steps: (1) completely dissolving a sodium-containing compound, a cesium-containing compound, and a holmium-containing compound in water to obtain a clear and transparent solution; wherein the molar ratio of the three is 1:2:1; (2) The clarified solution is heated until the solvent is evaporated; the heating temperature is 373-593 K; and lead-free perovskite Cs2NaHoBr6 powder is obtained.

[0025] Furthermore, the sodium-containing compound is sodium bromide; the cesium-containing compound is cesium bromide; and the holmium-containing compound is holmium bromide.

[0026] The lead-free perovskite Cs2NaHoBr6 provided by the present invention exhibits characteristic emission in the visible light-near infrared region under the excitation of ultraviolet light, blue light and near-infrared light; the luminescence intensity increases with the increase of temperature, showing good anti-thermal quenching behavior.

[0027] The present invention also provides a method for preparing the fractal structure of the lead-free perovskite Cs2NaHoBr6, that is, a growth method of the fractal structure perovskite, comprising the following steps: (1) dissolving the lead-free perovskite Cs2NaHoBr6 prepared by the above method in water to obtain a transparent solution; (2) Add 1-2 mL of anti-solvent to the transparent solution obtained in step (1) and mix well; (3) Dropping the solution obtained in step (2) onto a substrate material and crystallizing it at a fixed temperature to obtain a fractal-structured perovskite.

[0028] Furthermore, the usage ratio of lead-free perovskite Cs2NaHoBr6 to antisolvent is (100-300) mg: (1-2) mL.

[0029] Furthermore, the concentration of the transparent solution required for crystallization in step (1) is 50-100 mg / mL.

[0030] Furthermore, the anti-solvent in step (2) is anhydrous ethanol, isopropanol, n-propanol, acetone or tetrahydrofuran.

[0031] Furthermore, the substrate material in step (3) is ordinary glass, ITO glass, FTO glass, silicon wafer or silicon wafer containing an oxide layer.

[0032] Furthermore, the crystallization temperature in step (3) is specifically 293-373 K.

[0033] The present invention successfully synthesizes lead-free perovskite Cs2NaHoBr6 by a new solvent boiling method. Compared with the traditional fluorescent thermal quenching perovskite material, the lead-free perovskite of the present invention exhibits thermally enhanced red and near-infrared light emission under the excitation of ultraviolet light, blue light and near-infrared light, has up-conversion and down-conversion luminescence capabilities, and its emission peak intensity shows a positive correlation in the range of 293-593 K, showing abnormal anti-thermal quenching behavior. The efficient up-conversion luminescence characteristics make the material have a wide range of application potential in the fields of solar cells, photocatalysis, bioimaging and optical communications. In particular, in solar cells, the near-infrared components in sunlight can be effectively utilized through the up-conversion process to improve the photoelectric conversion efficiency of the battery. Under the excitation of short-wave ultraviolet light or blue light, red light and near-infrared light can be emitted, realizing down-conversion luminescence in a wide spectral range. Cs2NaHoBr6 powder was dissolved in an antisolvent and an in-situ solution crystallization method was used to prepare a fractal structure pattern with preferential orientation and self-similar characteristics, which significantly improved the temperature sensing performance of the compound. Its relative sensitivity increased from 1.14% K to 2.54%. -1 Enhanced to 2.60% K -1 , showing good application prospects in non-contact optical temperature measurement.

[0034] Example 1 A green preparation method of lead-free perovskite Cs2NaHoBr6 is as follows: (1) Dissolve cesium bromide (2 mmol, 0.4256 g), sodium bromide (1 mmol, 0.1029 g), and holmium bromide (1 mmol, 0.4046 g) in 2 mL of distilled water to obtain a clear solution. (2) Heating the clarified solution at 373 K for 90 min; (3) After the solution is evaporated to dryness, lead-free perovskite Cs2NaHoBr6 powder is obtained.

[0035] Figure 1 is the XRD pattern of the disordered powder of lead-free perovskite Cs2NaHoBr6 obtained in Example 1; it can be seen from the figure that the X-ray diffraction pattern and crystal structure of the lead-free perovskite Cs2NaHoBr6 obtained in this embodiment are as shown in the attached Figure 1 As shown, the three strong peaks all correspond well.

[0036] Example 2 A green preparation method of lead-free perovskite Cs2NaHoBr6 is as follows: (1) Dissolve cesium bromide (2 mmol, 0.4256 g), sodium bromide (1 mmol, 0.1029 g), and holmium bromide (1 mmol, 0.4046 g) in 3 mL of distilled water to obtain a clear solution. (2) Heating the clarified solution at 523 K for 50 min; (3) After the solution is evaporated to dryness, lead-free perovskite Cs2NaHoBr6 powder is obtained.

[0037] Figure 2 is the photoluminescence spectrum of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 2 under ultraviolet light and blue light excitation; Figure 3 2 is the photoluminescence spectrum of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 2 under near-infrared excitation; it can be seen from the figure that the lead-free perovskite Cs2NaHoBr6 powder obtained in this embodiment has a photoluminescence spectrum under different excitation light sources. Figure 2 and attached Figure 3 As shown, it can be seen that under the excitation of ultraviolet light, blue light and near-infrared light, there are emission peaks in the red light region ranging from 620-680 nm, indicating that the material has both up-conversion and down-conversion properties.

[0038] Example 3 A green preparation method of a lead-free perovskite luminescent material Cs2NaHoBr6 is as follows: (1) Dissolve cesium bromide (2 mmol, 0.4256 g), sodium bromide (1 mmol, 0.1029 g), and holmium bromide (1 mmol, 0.4046 g) in 4 mL of distilled water to obtain a clear solution. (2) Heating the clarified solution at 593 K for 40 min; (3) After the solution is evaporated to dryness, lead-free perovskite Cs2NaHoBr6 powder is obtained.

[0039] Figure 4 This is the up-conversion temperature-variable spectrum of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 3 under the excitation of a 980 nm light source; Figure 5 : is the down-conversion temperature-variable spectrum of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 3 under the excitation of a 460 nm light source; as can be seen from the figure, the up-conversion temperature-variable spectrum of the lead-free perovskite Cs2NaHoBr6 powder obtained in this embodiment is as shown in the attached figure. Figure 4 The down-conversion temperature spectrum is shown in the attached Figure 5 It is obvious that with the increase of temperature, the red light emission and near-infrared light emission intensities of the up- and down-conversion temperature-variable spectra are significantly improved, and both show excellent anti-thermal quenching behavior.

[0040] Example 4 A preparation method of fractal structure lead-free perovskite Cs2NaHoBr6 is as follows: (1) Weigh the lead-free perovskite Cs2NaHoBr6 (100 mg) prepared in Example 2 and dissolve it in 1 mL of water, stirring to obtain a transparent solution; (2) Add 1 mL of anhydrous ethanol to the transparent solution and mix well; (3) The solution in step (2) is dropped onto a glass slide made of ordinary glass and crystallized at 293 K to obtain a fractal-structured lead-free perovskite Cs2NaHoBr6.

[0041] Figure 6 is a scanning electron microscope photograph of the lead-free perovskite Cs2NaHoBr6 disordered powder obtained in Example 4; Figure 7 is a scanning electron microscope photograph of the fractal structure of the lead-free perovskite Cs2NaHoBr6 obtained in Example 4; Figure 8 The fractal structure of the lead-free perovskite Cs2NaHoBr6 obtained in Example 4 is a down-conversion temperature-dependent spectrum under the excitation of a 460 nm light source; as can be seen from the figure, the scanning electron microscope photos of the original powder sample and the fractal structure lead-free perovskite Cs2NaHoBr6 grown in this embodiment are shown in the attached figure. Figure 6 and attached Figure 7As shown in FIG. 1 , it can be observed that the fractal shape grown resembles the leaves of a fern, and there is similarity between the whole and the parts. The original powder presents a regular block morphology at a size of 1 μm. The down-conversion temperature-variable spectrum of the fractal structure lead-free perovskite Cs2NaHoBr6 grown in this embodiment under the excitation of a 460 nm light source is shown in the attached figure. Figure 8 As shown, it also exhibits reverse thermal quenching behavior with increasing temperature.

[0042] Example 5 A preparation method of fractal structure lead-free perovskite Cs2NaHoBr6 is as follows: (1) Weigh the lead-free perovskite Cs2NaHoBr6 (300 mg) prepared in Example 3 and dissolve it in 1 mL of water until it is completely dissolved to obtain a transparent solution; (2) Add 2 mL of isopropanol to the clear solution and mix well; (3) The solution prepared in step (2) is dropped onto a silicon wafer and crystallized at 373 K to obtain a fractal-structured lead-free perovskite Cs2NaHoBr6.

[0043] Fig. 9 : is a comparison diagram of the relative sensitivity of the fractal structure and disordered powder of the lead-free perovskite Cs2NaHoBr6 obtained in Example 5; it can be seen from the figure that the relative temperature sensitivity of the ordered fractal and disordered powder lead-free perovskite Cs2NaHoBr6 grown in this embodiment is as shown in the attached figure. Fig. 9 As shown in Figure 2, the fractal structure Cs2NaHoBr6 exhibits a high sensitivity to temperature changes. Compared with the disordered powder, the relative sensitivity of the ordered structure increases from 1.14% K to 2.54% K. -1 Enhanced to 2.60% K -1 . It shows that fractal structure can effectively improve the temperature sensing performance of materials.

[0044] Example 6 A preparation method of fractal structure lead-free perovskite Cs2NaHoBr6 is as follows: (1) Weigh the lead-free perovskite Cs2NaHoBr6 (100 mg) prepared in Example 1 and dissolve it in 1 mL of water until it is completely dissolved to obtain a transparent solution; (2) Add 1 mL of n-propanol to the transparent solution and mix well; (3) The solution in step (2) is dropped onto ITO glass and crystallized at 293 K to obtain fractal-structured lead-free perovskite Cs2NaHoBr6.

[0045] Example 7 A preparation method of fractal structure lead-free perovskite Cs2NaHoBr6 is as follows: (1) Weigh the lead-free perovskite Cs2NaHoBr6 (150 mg) prepared in Example 2 and dissolve it in 1 mL of water until it is completely dissolved to obtain a transparent solution; (2) Add 1 mL of acetone to the transparent solution and mix well; (3) The solution in step (2) is dropped onto FTO glass and crystallized at 353 K to obtain fractal-structured lead-free perovskite Cs2NaHoBr6.

[0046] Example 8 A preparation method of fractal structure lead-free perovskite Cs2NaHoBr6 is as follows: (1) Weigh the lead-free perovskite Cs2NaHoBr6 (300 mg) prepared in Example 3 and dissolve it in 1 mL of water until it is completely dissolved to obtain a transparent solution; (2) Add 2 mL of tetrahydrofuran to the clear solution and mix well; (3) The solution in step (2) is dropped onto a silicon wafer containing an oxide layer and crystallized at 373 K to obtain a fractal-structured lead-free perovskite Cs2NaHoBr6.

[0047] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing lead-free perovskite Cs2NaHoBr6, characterized in that: include: First, the sodium-containing compound, the cesium-containing compound and the holmium-containing compound are completely dissolved in water, then heated until the solvent is evaporated, and cooled to room temperature to obtain the lead-free perovskite Cs2NaHoBr6.

2. The method for preparing the lead-free perovskite Cs2NaHoBr6 according to claim 1, characterized in that: The molar ratio of the sodium-containing compound, the cesium-containing compound and the holmium-containing compound is 1:2:1; the sodium-containing compound is sodium bromide; the cesium-containing compound is cesium bromide; and the holmium-containing compound is holmium bromide.

3. The method for preparing the lead-free perovskite Cs2NaHoBr6 according to claim 1, characterized in that: The heating temperature is 373-593 K.

4. A lead-free perovskite Cs2NaHoBr6, characterized in that The method is prepared by any one of claims 1 to 3.

5. The lead-free perovskite Cs2NaHoBr6 according to claim 4, characterized in that The lead-free perovskite Cs2NaHoBr6 emits red light of 620-680 nm and near-infrared light of 950-1020 nm under the excitation of short-wave ultraviolet light or blue light; it emits red light of 620-680 nm and near-infrared light of 760-820 nm when excited by near-infrared light; the emission peak intensity of the lead-free perovskite Cs2NaHoBr6 shows a positive correlation in the range of 293-593 K.

6. The method for preparing the fractal structure of the lead-free perovskite Cs2NaHoBr6 according to claim 4, characterized in that: include: The lead-free perovskite Cs2NaHoBr6 is completely dissolved in water to obtain a transparent solution, and then an anti-solvent is added to disperse it evenly, placed on a substrate material, and after crystallization, an ordered fractal structure is obtained.

7. The method for preparing the fractal structure of the lead-free perovskite Cs2NaHoBr6 according to claim 6, characterized in that: The solubility of the transparent solution is 50-100 mg / mL; the dosage ratio of the lead-free perovskite Cs2NaHoBr6 to the anti-solvent is (100-300) mg: (1-2) mL.

8. The method for preparing the fractal structure of the lead-free perovskite Cs2NaHoBr6 according to claim 6, characterized in that: The anti-solvent is anhydrous ethanol, isopropanol, n-propanol, acetone or tetrahydrofuran; the substrate material is ordinary glass, ITO glass, FTO glass, silicon wafer or silicon wafer containing an oxide layer; and the crystallization temperature is 293-373 K.

9. A fractal structure of a lead-free perovskite Cs2NaHoBr6, characterized in that: The preparation method according to any one of claims 6 to 8 is used to prepare the lead-free perovskite Cs2NaHoBr6, and the relative sensitivity is increased from 1.14% K -1 Enhanced to 2.60% K -1 .

10. Application of the fractal structure of lead-free perovskite Cs2NaHoBr6 prepared by the preparation method according to any one of claims 6 to 8 in the preparation of up-conversion luminescent materials, down-conversion luminescent materials and temperature sensing materials.

Citation Information

Cited By

  • Temperature-sensitive fluorescent powder with positive and negative thermal quenching characteristics as well as preparation method and application of temperature-sensitive fluorescent powder

    CN121406327A